Tanggung Jawab Negara Terhadap Pencemaran Laut Akibat Tumpahan Minyak Di Karawang Berdasarkan Hukum Nasional Dan Internasional - Via Enjelina; Vina Aulia Dwi Putri; Viony Nabilla Cahaya Radika; Muhammad Hasan (GLOBAL SCIENTS PUBLISHER, 2026)
The state’s responsibility for marine pollution caused by oil spills in Karawang based on national and international legal provisions includes efforts of prevention, reduction, control, and handling of pollution. This incident occurred twice, namely in 2019 which was caused by a leak in the YYA-1 well and again in 2021 due to a leak in an underwater pipeline. This research uses a normative legal research method with a statutory approach, a conceptual approach, and a case approach. The results of the study show that the implementation of state responsibility for marine pollution caused by oil spills in Karawang is still not optimal. Therefore, strict law enforcement is needed to protect the marine environment and ensure the community’s right to a good and healthy environment.